2021
DOI: 10.15835/nbha49212310
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical, physiological and molecular evaluation reveals superior salt-tolerance in bread wheat through salt-induced priming approach

Abstract: Salt stress significantly limit wheat crop productivity worldwide. Exposure to non-lethal levels of salt stress, referred to as "salt-priming", allows plants to persist subsequent lethal conditions; the priming effect continues even after an extended salt stress-free period. This study attempted to evaluate the effectiveness of the salt-induced priming approach to cope with the toxic effects of long-term salinity stress in wheat. After 22 days of gradual salt acclamation to reach 250 mM NaCl, plants were recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…It has been observed that a high quantity of proline protects plants from osmotic stressors by stabilizing numerous functional units such as complex II electron transport, membranes, proteins, and enzymes as RUBISCO [66]. In harmony with these results, an increase in proline accumulation was documented in wheat [8], pearl millet [62] and Pisum sativum [13].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been observed that a high quantity of proline protects plants from osmotic stressors by stabilizing numerous functional units such as complex II electron transport, membranes, proteins, and enzymes as RUBISCO [66]. In harmony with these results, an increase in proline accumulation was documented in wheat [8], pearl millet [62] and Pisum sativum [13].…”
Section: Discussionmentioning
confidence: 73%
“…More than 7% of total land and about 20% of arable lands are harmed by salinity, particularly in arid and semi-arid regions such as Egypt [7]. Furthermore, most of world arable lands (>50%) are predicted to be salinized by 2050 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The heatmap and PCA were drawn with aid of ClustVis. tool [85,86] and JavaScript script language [87].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ALA and Cys are effective priming molecules and bear agronomic importance in improving wheat yield in the arid cultivable regions. Priming for drought or salinity allows stress tolerance and offers several benefits in many crops [93]. This improvement was extended to the grain processing technology by affecting the alveographic parameters (Tables 8 and 9).…”
Section: Discussionmentioning
confidence: 99%